Influence of ocean circulation and benthic exchange on Deep Northwest Atlantic Nd isotope records during the past 30,000 years - Pöppelmeier, Frerk; Blaser, Patrick; Gutjahr, M.; Süfke, Finn; Thornalley, D. J. R.; Grützner, J.; Jakob, Kim; Link, Jasmin; Szidat, S.; Lippold, Jörg (Geochemistry, geophysics, geosystems, 2019)
Neodymium (Nd) isotopes extracted from authigenic sediment phases are increasingly used as a proxy for past variations in water mass provenance. To better constrain the controls of water mass provenance and nonconservative effects on the archived Nd isotope signal, we present a new depth transect of Nd isotope reconstructions from the Blake Bahama Outer Ridge along the North American continental margin covering the past 30 ka. We investigated five sediment cores that lie directly within the main flow path of the Deep Western Boundary Current, a major advection route of North Atlantic Deep Water. We found offsets between core tops and seawater Nd isotopic compositions that are observed elsewhere in the Northwest Atlantic. A possible explanation for this is the earlier suggested redistribution of sediment by nepheloid layers at intermediate as well as abyssal depths, transporting material downslope and along the continental margin. These processes potentially contributed to Nd isotope excursions recorded in Northwest Atlantic sediment cores during the Bølling-Allerød and early Holocene. An Atlantic-wide comparison of Nd isotope records shows that the early Holocene excursions had an additional contribution from conservative advection of unradiogenic dissolved Nd. Nevertheless, the trends of the Nd isotope records are in general agreement with previous reconstructions of water mass provenance from the entire Atlantic and also reveal millennial-scale changes during the last deglaciation in temporal high resolution, which have rarely been reported before. Further, the new records confirm that during cold periods the Northwest Atlantic was bathed by an increased contribution of southern sourced water.
Gesehen am 04.02.2020